Blast Off!: Poems About Space - Hopkins, Lee Bennett; Sweet, Melissa (New York : HarperCollins Publishers, 1995)
A collection of poems about the moon, stars, planets, astronauts, and related wonders.
Keywords: Children's poetry, American; American poetry -- Collections; Early chapter book; Outer space -- Juvenile poetry; Outer space -- Poetry; Early chapter book